EVALUATION OF THE FOURTH VENTRICLES OF ADULTS IN NORTH-EASTERN NIGERIANS USING COMPUTERIZE TOMOGRAPHIC IMAGES - Amaza DS; Zirahei JV; Sambo N; Oyewale AA; Kogi GA (Ntec Specialist, 2020)
Background: Knowledge of anatomy of the fourth ventricle and the structures around it, is significant in sex determination, surgical operations and brain disorders. Accurate measurements of the fourth ventricle are needful in evaluating brain disorders and in decision making before any neurosurgical procedures. Objective: To determine the dimensions of the apparently normal fourth ventricles and compare the parameters among males and females with a view to providing baseline data. Method: Retrospective study was carried out on brain CT images. Six hundred (600) brain CT images of adult North-eastern Nigerians (350 males and 250 females) were measured. The age range for the individuals was 18-75years. The brain CT images for males and females were classified separately into six (6) age groups spanned eight (8) years interval. Measurements were done using Dicomworks software. The software provides a meter rule with which measurements were done, based on a standard method. Greatest height of fourth ventricle was measured from the roof and floor of the fourth ventricle while the width measured at the midpoint of the ventricle. Results: The height of the fourth ventricle was larger in males (9.95 mm ± 1.04) as compared to females (8.38 mm ± 1.69). The width of the fourth ventricle was also observed to be greater in males (12.95 mm ±1.29) than in females (11.67 mm ±1.45). Thus, the difference between the lengths and widths of the fourth ventricles were higher and statistically significant (p less than 0.05) among males and females. Conclusion: The present study concludes that the parameters of the 4th ventricle measured were sexually dimorphic and can be used in sex determination in the sample population. This study also has provided reference point for the normal values of the length and width of the fourth ventricle in male and female Nigerians.